A Systematic List of Mammals Reported from Kerala, India - Cheruvat, Dinesan; Radhakrishnan, C.; Palot, Muhamed Jafer (Indian Forester, 2004)
There are 408 species of Mammals known till date from India. An updated systematic list of mammals known so far from the State of Kerala incorporating information on 109 species, including 96 species of terrestrial and 13 species of aquatic mammals, is presented. The list also provides the vernacular name, common English name and scientific name of each species besides data on their distribution as well as conservation status.